Efektifitas Sun Protection Factor secara In Vitro Sediaan Krim Ekstrak Etanol Akar Kelakai (Stenochlaena palustris Bedd) Asal Kalimantan Tengah: Effectiveness of Sun Protection Factor In Vitro Preparation of Kelakai Root Ethanol Extract (Stenochlaena palustris Bedd) Origin Central Kalimantan - Risqika Yuliatantri Paramawidhita; Shesanti Citrariana; Dita Sumasfida (Jurnal Surya Medika (JSM), 2022)
Kalimantan is an island in Indonesia with many medicinal plants, one of which is the Kalakai plant. Kalakai contains several bioactive compounds, such as phenolic, flavonoids, alkaloids, and terpenoid families. The roots of the Kalakai plant (Stenochlaena palustris Bedd) are considered to have the potential as sunscreens. This study aims to determine the roots of Kalakai were formulated in the form of cream with a ratio of extract concentrations of 1%, 2%, and 3%. The cream's physical properties (organoleptic, homogeneity, spreadability, pH, and adhesion) were evaluated on day 1, day 7, and day 14. The good physical properties formula of sunscreen cream was tested for SPF value. This study used an experimental method. The results showed that it could be formulated in cream and the physical evaluation of the cream showed no statistically significant differences between formulations I, II, and III. The sun protection factor values obtained from the creams in formulation II, with extracts of 2% at concentrations of 300 ppm and 350 ppm, are 11 and 12. The results are classified as maximum protection abilities.